2012
DOI: 10.1136/archdischild-2012-302104
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of sleep-disordered breathing symptoms and respiratory events in infants with cleft lip and/or palate

Abstract: The results highlight that infants across the spectrum of CL/P have a high risk of SDB symptoms and obstructive respiratory events before palate surgery. Clinicians should enquire about symptoms of SDB and consider investigation with polysomnography in all infants with CL/P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 48 publications
(33 reference statements)
3
68
1
5
Order By: Relevance
“…In achondroplasia, we reported a very weak correlation between clinical signs and PSG results 6 . One particularly interesting study compared sleep data in 12 infants with Sleep-disordered breathing is also very frequent in case of cleft palate, with severity increasing from isolated cleft to syndromic cleft to PierreRobinsequence 9 ( fig.1 and fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…In achondroplasia, we reported a very weak correlation between clinical signs and PSG results 6 . One particularly interesting study compared sleep data in 12 infants with Sleep-disordered breathing is also very frequent in case of cleft palate, with severity increasing from isolated cleft to syndromic cleft to PierreRobinsequence 9 ( fig.1 and fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Infants with cleft lip and or palate have a higher incidence of airway obstruction and sleep disordered breathing. 7 Even in the presence of a single underlying anatomic defect as cleft lip, it is prudent to look for possible coexistent etiologies contributing to OSA which could be treatable. Our patient also had laryngomalacia and recurrent respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of 50 infants found a mean obstructive AHI of 7.6/h in those with non-syndromic CLP. 62 One of the difficulties in determining the prevalence of and risk factors for OSAS in the CLP population is the inherent heterogeneity of presentation in these children.…”
Section: Cleft Lip/palatementioning
confidence: 99%